Peran Publik Figur Dalam Optimalisasi Penghimpunan Zakat, Infaq dan Sedekah di Kabupaten Tolitoli - Khair, Fathul (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2021)
The role of the zakat agency is very important to restore the trust of the natural community to carry out their obligations as a Muslim. The application of strategies in collecting zakat, infaq, and alms funds is very much needed, one of which is by cooperating with public figures to become marketing media for zakat amil. Public figures are required to provide good education for the community, especially public figures in the field of religion, because many of their activities are public spectacle. Therefore, public figures are expected to be examples for the community because they can influence public decisions in general. This research is descriptive research. Descriptive research is research that seeks to provide a systematic and careful description of the actual facts and characteristics of a particular population. The role of public figures can boost the collection of zakat, infaq and alms funds. Many muzakki claim to know public figures, rather than know their institutions. In fact, some of the muzakki trust public figures more than the amil zakat institutions. Some of these muzakki prefer to pay zakat, infaq, and alms funds through these public figures rather than paying them to zakat, infaq and alms amil funds.